Analisis Pengaruh Lingkungan Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan (Studi Kasus Kantor Diskopindag UPT Pasar Kota Malang) - Tri Sry Rejeky Sembiring; N. Rachma; M. Khoirul Anwarudin Broto Suharto (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The purpose of this study was to determine the impact of work environment and work discipline on employee performance. This study uses quantitative research with descriptive categories. The survey sample consisted of his 75 respondents drawn from a formula based on Malhotra's theory. The analytical technique used in this study is multiple linear regression using SPSS 22. The results of this study show that work environment and work discipline simultaneously have a significant positive impact on employee performance. The working environment has a significant positive impact on employee performance. Work discipline clearly has a positive impact on employee performance. Keywords: Work Environment, Work Discipline, Employee Performance